Perancangan dan Implementasi Sistem Informasi Berbasis Web untuk Usaha Coffee Shop Menggunakan Teknologi PHP, CSS, dan Bootstrap - Praditya, I Made Bayu; Febriantika, I Kadek Heri; Putra, Agus Kadek Dwiq Septiana; Wijaya, I Gede Sathya Adi; Candrananda, Made Aditya; Sanjaya, I Gede Wahyu (Journal Informatics Nivedita, 2025)
The advancement of digital technology has encouraged business actors, including the coffee shop sector, to adapt through the implementation of web-based systems. However, many coffee shops still face challenges in ordering processes, product data management, and transaction recording, which are often done manually, thereby reducing operational efficiency. This study aims to design and implement a web-based information system that facilitates product ordering, inventory management, and digital transaction recording. The system was developed using PHP as the backend programming language, along with CSS and Bootstrap for a responsive user interface. The development method used is the System Development Life Cycle (SDLC) with the Waterfall model, which includes the stages of requirement analysis, design, implementation, and testing. Testing was conducted using the black-box method to ensure that each feature functions properly. The test results showed a validation rate of 100%, indicating that the system operates optimally and is ready for use. Therefore, this information system is expected to help coffee shops manage their business activities more efficiently, accurately, and systematically.